Effect of BI Rate, Inflation and Index Dow Jones Against Jakarta Islamic Index (JII) - Septy Setia Nugraha; Iwan Setiawan (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2019)
The capital market in Indonesia is developing with the presence of the Islamic capital market through a collaboration between the Indonesia Stock Exchange and PT. Danareksa Investment Management by launching the Jakarta Islamic Index (JII) on July 3, 2000. The existence of Islamic mutual funds emerged as an answer to the concerns of Muslim investors regarding interest, speculation, and unclear investment in mutual funds. This study aimed to estimate the effect of inflation, BI Rate, Exchange Rate and Dow Jones Industrial Average Index on the Jakarta Islamic Index (JII). This study uses secondary data based on time series from Quarter 1: 2008-Quarter 4: 2018, obtained from the Indonesia Stock Exchange, Bank Indonesia, the Indonesian Central Bureau of Statistics and Financial Economics and Statistics. The analytical method used for this study uses an analytical approach multiple linear regression. Based on the simultaneous test shows that the Inflation, BI Rate, Exchange Rate and Dow Jones Index influence together on JII. Based on the results of the study it was found that the Inflation variable partially and significantly affected JII